L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Collection Les Entêtées, 1983)
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

The Amazing decade: women and performance art in America : 1970-1980 - Roth, Moira; Jacob, Mary Jane; Roth, Moira (Astro Artz., 1983)
"This book is a detailed study of the powerful and innovative role women artists played in the development and expansion of performance art. This hybrid art form, which combines the visual arts with ingredients drawn from experimental dance, theater, music, and poetry, emerged in the late 1960's at the same time as the women's movement. Many women artists turned to performance art in order to translate and capture visually the concerns, demands and visions of the women's movement; thus women led the way in performance art's explorations of autobiography, ritual, mass spectacle and the creation of characters and personae. The Amazing Decade, edited by Moira Roth, with an introduction by Mary Jan Jacob, culls the best from women's performance history, highlighting pivotal works, chronicling changes and projecting future directions: the book contains a major essay by Roth on the history and character of women's performance art; individual profiles on thirty-seven artists and collectives; an extensive bibliography; and a year-by-year chronology from 1956 onward in which women's performance art is set in the context of history and the women's movement. Profusely illustrated, The Amazing Decade is an indispensable reference book and an invaluable teaching tool"--
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis